2018
DOI: 10.15517/rac.v43i1.35670
|View full text |Cite
|
Sign up to set email alerts
|

Absorción de nutrientes en palma aceitera variedad "Compacta X Ghana" en vivero

Abstract: Se calculó la absorción de nutrimentos en la variedad Compacta x Ghana en viveros de Elaeis guineensis en la región sur de Costa Rica. Se utilizó una sección de vivero de la empresa Palma Tica S.A. de aproximadamente 5 000 plantas y se brindó un estado de suficiencia nutricional durante 300 días después de siembra (dds). Se seleccionaron plantas mediante el cálculo de intervalo de confianza según la desviación estándar y el tamaño de la muestra a un alfa de 0,01, para las variables diámetro de bulbo y largo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The results obtained were similar to the findings of Soratto, Fernandes and Souza-Schlick (2011), who showed that large amounts of Mn accumulate in the leaves and stems of potato plants and perform various functions in metabolism, such as activating enzymes in the respiration process and water photolysis during photosynthesis (Cabalceta, Saldias, & Alvarado, 2005). Additionally, high levels of Mn might accumulate due to its low mobility in plant tissues.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained were similar to the findings of Soratto, Fernandes and Souza-Schlick (2011), who showed that large amounts of Mn accumulate in the leaves and stems of potato plants and perform various functions in metabolism, such as activating enzymes in the respiration process and water photolysis during photosynthesis (Cabalceta, Saldias, & Alvarado, 2005). Additionally, high levels of Mn might accumulate due to its low mobility in plant tissues.…”
Section: Resultssupporting
confidence: 90%
“…Boron (B) is required for potato cultivation, particularly during the early stages of tuber formation. They promote the growth and division of meristematic tissues, the development of the cell wall, and the translocation of starch from the aerial parts to the tubers (Cabalceta, Saldias, & Alvarado, 2005).…”
Section: Resultsmentioning
confidence: 99%